PENGUATAN KARAKTER KEJUJURAN MELALUI PEMBELAJARAN AGAMA KATOLIK BERBASIS NARATIF-EKSPERIENSIAL - Delviana Sawo Delvin; Alfonsus Mudi Aran (Lembaga Penelitian STKIP Widya Yuwana, 2026)
This research investigates the effectiveness of the narrative-experiential approach in shaping the character of honesty among students at SD Inpres Lewolere through Catholic Religious Education (CRE). Character education is essential in creating individuals who are not only intellectually capable but also morally responsible. However, the current state of education highlights a crisis in character, particularly in terms of honesty, as seen in incidents of cheating, plagiarism, and falsifying signatures. This indicates that academic education, which has been prioritized, has not yet fully succeeded in forming individuals with strong moral integrity. Honesty, a core value in Catholic teachings, is integral to developing healthy relationships and a dignified life. Despite this, the traditional teaching methods, especially in Catholic Religious Education, tend to be conventional, focused on lecturing, and lack the depth necessary to evoke true moral awareness among students. The narrative-experiential approach, which blends storytelling with direct personal experience, offers a transformative pedagogical model. By combining religious narratives with experiential learning, this method helps students not only understand moral values cognitively but also internalize them emotionally and spiritually. Previous research supports that this approach can effectively instill values like honesty, as it encourages students to reflect on and apply these values in real-life contexts. The study was conducted over four months at SD Inpres Lewolere, involving interviews and reflective activities with both a teacher and six students. The findings suggest that the narrative-experiential approach significantly impacts students’ ability to internalize and apply the value of honesty. It fosters active participation, moral reflection, and behavioral transformation. The study concludes that integrating narrative and experiential learning in CRE can be highly effective in character education, particularly in instilling honesty among students. This approach, when consistently applied, leads to the holistic development of students' character, integrating moral understanding, emotional reflection, and concrete actions.